The Comparison of Verb Use in Social and Science Research Article Abstract A Corpus-Based Study - Suwandi, Suwandi (CV. Rayyan Dwi Bharata, 2024)
A research article is a kind of academic writing that is extensively utilized by scientists to explain their thoughts in the present day. This paper focuses on the abstract part since it is an important representation of the substance of an academic paper. This study intends to compare the verb use in abstracts of scientific and social research articles. To examine this conversation, qualitative descriptive research is performed in this study. This research investigates the frequency of the verbs identified by LancsBox 6.0 using corpus analysis. This research employs 15 scientific abstracts and 15 social abstracts produced by Indonesian authors and published between April 1st until September 30th, 2021 in order to determine the most and least commonly utilized verb types in each study. This study's objectives are to determine the types of verbs used in science and social article abstracts, to determine the frequency of verb use in science and social article abstracts, and to explain why x types of verbs are the most and y types are the least prevalent in science and social research article abstracts. Material, relational, cognitive, possessive/relational, perception/relational, feeling, existential, verbal, and corporeal are the verb kinds utilized in abstracts of scientific and social research articles, according to the study's findings. In both scientific and social abstractions, the material verb type that conveys a definite meaning is used most often. In contrast, corporeal, which expresses subjective meaning, is utilized least often in abstracts of scientific and scholarly articles. It may be argued that material verbs are most commonly utilized in academic writing that requires an objective statement as a defining property of the genre.